-15t+15+9t=7t-4

Simple and best practice solution for -15t+15+9t=7t-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15t+15+9t=7t-4 equation:


Simplifying
-15t + 15 + 9t = 7t + -4

Reorder the terms:
15 + -15t + 9t = 7t + -4

Combine like terms: -15t + 9t = -6t
15 + -6t = 7t + -4

Reorder the terms:
15 + -6t = -4 + 7t

Solving
15 + -6t = -4 + 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
15 + -6t + -7t = -4 + 7t + -7t

Combine like terms: -6t + -7t = -13t
15 + -13t = -4 + 7t + -7t

Combine like terms: 7t + -7t = 0
15 + -13t = -4 + 0
15 + -13t = -4

Add '-15' to each side of the equation.
15 + -15 + -13t = -4 + -15

Combine like terms: 15 + -15 = 0
0 + -13t = -4 + -15
-13t = -4 + -15

Combine like terms: -4 + -15 = -19
-13t = -19

Divide each side by '-13'.
t = 1.461538462

Simplifying
t = 1.461538462

See similar equations:

| 5r-10=2k | | y=1/3cos3x | | 5b+2a-3b= | | 3/4:2 | | (50+2x)(30+2x)-1500=425 | | 5/8÷3/4= | | (50+2x)(30+2x)-150=425 | | 5s-7/=7 | | 2/9×7/6 | | 4K+12=2k | | (50+x)(30+x)-150=425 | | a+3a-2a-2b= | | 20logx=32.5 | | 12h-15=9h | | a+5a+b= | | 6a-5a+4b= | | 3x-y=20x+2y=23 | | 8m-12=5m | | 81x^8-82x^4+1=0 | | 2X+4.5Y=10 | | (D^3-3D^2+4)x=0 | | x^2+14x+14+y^2-2y=0 | | Y=-0.7x+340 | | 8x^3-12x^2-2x+3=0eq | | 10(s-8)=-125 | | (40-x)(16-x)=340 | | 12-1/3x=x | | 33-4x=9-9x | | 300-56x-x^2=0 | | x=12-1/3x | | 3x-4=11x-67 | | 0.56x+x=220 |

Equations solver categories